2014
DOI: 10.1136/neurintsurg-2014-011212
|View full text |Cite
|
Sign up to set email alerts
|

M1 is not M1 in ischemic stroke: the disability-free survival after mechanical thrombectomy differs significantly between proximal and distal occlusions of the middle cerebral artery M1 segment

Abstract: Proximal occlusions of the M1 segment of the MCA incorporating the lenticulostriate perforators are associated with a poorer clinical outcome than distal M1 occlusions that spare these perforators. Involvement of these perforators might become an additional predictor of clinical outcome after mechanical thrombectomy in ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 18 publications
3
36
1
2
Order By: Relevance
“…The 90-day mortality rate was 55.6% in patients with DT<5 mm and 4.8% in patients with DT>30 mm (P=0.007; Figure 3A and 3B). There was no significant correlation using Spearman ρ between DT and the short-term change in neurological status (R=0.037; P=0.696), defined as the difference between the initial NIHSS score and the NIHSS score on day 7 after IVT (eg, DT<5 mm: NIHSS score improvement 4 [−2 to 8]; DT>30 mm: NIHSS score improvement 3 [1][2][3][4][5][6][7][8][9][10]). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 90-day mortality rate was 55.6% in patients with DT<5 mm and 4.8% in patients with DT>30 mm (P=0.007; Figure 3A and 3B). There was no significant correlation using Spearman ρ between DT and the short-term change in neurological status (R=0.037; P=0.696), defined as the difference between the initial NIHSS score and the NIHSS score on day 7 after IVT (eg, DT<5 mm: NIHSS score improvement 4 [−2 to 8]; DT>30 mm: NIHSS score improvement 3 [1][2][3][4][5][6][7][8][9][10]). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they used a complicated analytic method based on evaluation of 4D-CTA images on dedicated workstations, which makes clinical application of their method in the acute setting difficult. In another angiography-based study, Behme and colleagues 10 analyzed patients treated by mechanical thrombectomy after M1 occlusion. They split the location of the M1 occlusion into 2 groups: a proximal group with occlusion of the lenticulostriate perforators visible on digital subtraction angiography, and a distal group without occlusion of the lenticulostriate perforators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The exact thrombus location, being more proximal or distal within the MCA M1 segment, was demonstrated to be a significant determinant for clinical outcome, however not for recanalization success. 18 To date, no evidence of vessel anatomy influencing recanalization success exists, though experienced interventionalists report that MT with stent retrievers is less likely to be successful in patients with strongly curved vessels. Zhu et al 19 reported that vessel branching and curvature are important determinants of recanalization success; however, their work was based on indirect MR imaging findings and focused on thrombectomy by using the Merci retriever (Concentric Medical, Mountain View, California), a first-generation device, which is now obsolete in most cases.…”
mentioning
confidence: 99%